Effect of integrated nutrient management on seed yield and quality in okra (Abelmoschus esculentus) - KUMAR, ASHWANI; PANDITA, V K (The Indian Journal of Agricultural Sciences, 2015)
Organic manures and biofertilizers improve soil, physical, chemical and biological properties and thus enhancecrops productivity and quality. Hence a study was carried out to assess interactive effect of inorganic fertilizers, vermicompost, Vesicular Arbuscular Mycorhizae (VAM) and biofertilizers [Azotobactor and Phosphate solubilizing bacteria (PSB)] inoculation on seed yield and quality of okra (Abelmoschus esculentus (L). Moench). The experiment was conducted in a randomized block design for two consecutive cropping season, kharif 2012 and 2013, with ten INM treatments including control (100% RDF). The INM treatments differed significantly for plant height, seed yield, number of pods/plant, number of seeds/pod and seed quality parameters. Integrated use of 100% RDF or NPK + BF (Biofertilizer mixture of Azotobactor + PSB + VAM 10 kg/ha) + vermicompost 2.5 t/ha (7.96, 7.25 q/ha) performed significantly better than the control (7.11, 5.95 q/ha) for seed yield and its attributes as well as seed quality parameters during kharif 2012 and 2013, respectively. Treatment 50% RDF + BF was found to be the least performer. Also, the mean cost benefit ratio (1.75) was highest for 100% RDF + BF + vermicompost. The highest average net returns (Rupees 40 510/ha) was obtained with (T8) the conjunctive use of inorganic fertilizer (100% NPK) and organic manure (vermicompost) and VAM along with bio-inoculants followed by 100% NPK + biofertilizers (Rupees 35 410/ha), 100% RDF (Rupees 34 190/ha) and lowest by 50% RDF + biofertilizers (Rupees 19 530/ha).